Biosorption of Nickel (II) from Aqueous Solutions onto Pistachio Hull Waste as a Low-Cost Biosorbent - Majid Zamani Beidokhti; Seyed Taghi Omid Naeeni; Mohammad Sajjad AbdiGhahroudi (Civil Engineering Journal, 2019)
There are many different industrial wastewater containing heavy metals that contribute to environmental pollution and raw agricultural waste is an effective adsorbent for the removal of heavy metals. The adsorption behavior of pistachio hull powder (PHP) as a low-cost adsorbent, with respect to nickel (II) ions, has been studied in order to consider its application to the purification of metal finishing wastewater. In this work, adsorption of nickel on pistachio hull has been studied by batch techniques. The adsorption depends on the process time, the pH of the solution, initial concentration of metals and the adsorbent concentration in the suspension. The kinetics of adsorption were relatively fast, reaching equilibrium for less than 60 minutes. Kinetic and isotherm modeling studies demonstrated that the experimental data best fit a pseudo-second order and Freundlich model, respectively. The maximum Langmuir adsorption capacity was 14 mg/g. The optimum pH required for maximum adsorption was found to be 4-6. The initial concentration of the adsorbate and the concentration of pistachio hull strongly affect the process. No influence of particle size was evidenced. A degree of adsorption higher than 75% can be achieved for nickel (II) ions.